Meckel-gruber syndrome associated with gastrointestinal tractus anomaly - Ergür, Ayça Törel; Taş, Fikret; Yıldız, Esin; Kılıç, Fikriye; Sezgin, İlhan (The Turkish Journal of Pediatrics, 2004)
Meckel-Gruber syndrome (MGS) is rare autosomal recessive disorder characterized by occipital encephalocele, postaxial polydactyly and polycystic kidneys. A one-day-old girl was admitted to our clinic with occipital encephalocele, polydactyly, ulnar deviation of left hand and failure to thrive. Patient’s parents were first-degree relatives. It was learned that the patient’s two sisters had died from similar anomalies. In our case, prenatal sonographic examination revealed oligohydramnios and hydrocephaly in the 33rd week of gestation. At birth her weight was 2200 g. Both physical and radiological examinations diagnosed MGS. Cranial computed tomography (CT) showed agenesis of cerebellar vermis and corpus callosum, and cystic dilatation of the 4th ventricle and lateral ventricles. The case died due to severe respiratory distress in the Intensive Care Unit on day 38. In the postmortem examination, longitudinally located intestine-like stomach was determined without a fundus. In conclusion, intestinal malrotation and hepatic portal fibrosis have been reported in MGS in the literature. In this case, a longitudinally located intestine-like stomach in MGS is reported for the first time. No such association to our knowledge has been previously reported.